Multiple directorships and the monitoring role of the board of directors: evidence from Malaysia - Hasnah Kamardin,; Rohaida Abdul Latif,; Kamarun Nisham Taufil Mohd,; Noriah Che Adam, (Penerbit Universiti Kebangsaan Malaysia, 2014)
This study aims to examine the relationship between multiple directorships and the monitoring role of the board of directors in Malaysian listed companies (PLC). The monitoring role is proxied by the percentage of directors’ attendance in board meetings, as attending meetings provides directors with resources about the management actions and assists directors to exercise their role effectively. The study uses a sample of 1023 directors from 134 companies on the Main Market of Bursa Malaysia (Malaysian Bourse) in year 2008. The results of the study show that the incidence of multiple directorships is low. Independent directors are found to have more multiple directorships. Directors with multiple directorships are older directors, have less director ownerships and are on boards with a high fraction of independent directors. Based on the 75% cut-off for the percentage of meetings’ attendance, the logistic regression suggests that no agency cost is associated with multiple directorships. However, the tendency to be absent from board meetings is associated with the high number of board meetings whilst the tendency to attend more board meetings is associated with the increase in age, tenure, and director ownership.